THE EFFECTS OF FLOOR TILES MADE FROM RECYCLED PLASTICS, BOTTLES, GLASS WASTE, AND COMPOSITE MATERIALS - M. A, Abubakar; H. K, Yunusa; Adamu, Sagir, G; U. M, Disina; A. A., Daheer (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2025)
Conventional ceramic and porcelain tiles, despite their widespread use, exhibit relatively high thermal conductivity (ranging from 0.60 to 1.50 W/m·K), making them prone to absorbing and transmitting cold during winter, which can lead to indoor discomfort and increase the risk of cold-related health issues such as hypothermia, arthritis flare-ups, and respiratory infections, especially among vulnerable populations. To address these limitations, this study explores the development of sustainable composite floor tiles using recycled plastic waste, Doum palm shell, glass waste, and silica sand. Six composite samples (A–F) were produced using the compression molding method, involving mixing, heating, and pressing the materials into tile forms. The samples were evaluated for mechanical properties (tensile, flexural, impact, hardness, and compressive strength), physical properties (water absorption and density), and thermal conductivity. Among them, Sample D recorded the highest mechanical strength (tensile: 16.3 MPa; compressive: 32.8 MPa), while Sample A showed the best insulation performance with the lowest thermal conductivity (0.198 W/m·K), lowest density (1.08 g/cm³), and minimal water absorption (0.72%). Compared to conventional tiles, the developed composites are more thermally efficient, lightweight, and moisture-resistant, making them a viable, eco-friendly alternative for use in cold-prone environments and sustainable, energy-conscious construction. It is recommended that the most promising formulations be further refined for commercial applications and integrated into environmentally responsible building practices.